Inter-Individual Budburst Variation in Fagus sylvatica Is Driven by Warming Rate - Malyshev, Andrey V.; van der Maaten, Ernst; Garthen, Aron; Maß, Dennis; Schwabe, Matthias; Kreyling, Juergen (Frontiers in Plant Science, 2022)
Abstract Onset of the growing season in temperate forests is relevant for forest ecology and biogeochemistry and known to occur earlier with climate change. Variation in tree phenology among individual trees of the same stand and species, however, is not well understood. Yet, natural selection acts on this inter-individual variation, which consequently affects the adaptive potential to ongoing environmental changes. Budburst dates of 146 mature individuals of Fagus sylvatica, the dominant natural forest tree of central Europe, were recorded over 12 years in one forest stand of 1 ha in the Müritz National Park, Germany. Tree-specific location, topographical differences as well as social status were measured to explain inter-individual variation in budburst. Furthermore, inter-individual differences in bud dormancy were quantified. Additional phenology and weather data across Germany from 405 sites over a 25-year period was used to put the insights from the single stand into perspective. Consistent phenological ranking over the years with respect to early and late flushing trees was observed within the single forest stand, with 23 trees consistently flushing three to six days earlier and 22 trees consistently flushing three to ten days later than the median. Trees flushing consistently early varied most in their spring budburst dates and were less dormant than late-flushing trees already in mid-winter. Higher variation in earlier flushing trees was best explained by a slower warming rate during their budburst in the observed stand as well as across Germany. Likewise, years with a lower warming rate during the budburst period were more variable in budburst dates. Early-flushing trees have a higher variation in spring phenology. The rate of warming during spring times is crucial to accurately project future within-species variation and the resulting adaptive potential in spring phenology of dominant forest tree species.